Biomotor Analysis of Physical Condition of Male Fencer Athletes Of Situbondo Regency - Kanadela, Sigy; Kartiko, Dwi Cahyo; Ismalasari, Rini; Hidayat, Rakhmat Nur (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
Fencing is a complex martial art because some special techniques and tactics involve the use of weapons for hand ability and agility in cutting, attacking, blocking, stabbing and also defending movements. Biomotor is a human movement that is influenced by the internal organ system, namely the respiratory system, neuromuscular, digestive, circulatory, energy, joints and bones. The type of research is quantitative descriptive. The subjects of the study were 32 male fencing athletes from Situbondo Regency. Measurements of the biomotor test of physical conditions include speed, strength, flexibility, endurance, explosive power, balance coordination, agility, and accuracy. The results of the analysis of the average speed of 5.16 sec. Average arm strength 26.75 times/minute. Average leg strength 111.41 kg. Average sit & reach flexibility is 33.14 cm, ankle flexibility of the right leg 14.71 cm, left leg 16.31 cm, upper body flexibility right 0.09 cm, left 1.19 cm, and full 0 cm. Average endurance 42.25 ml/kg/min. The average arm explosive power is 172.74 watts. The average leg explosive power is 19.08 watts. Average balance 16.55 sec. Average coordination 4.98 sec. Average agility 11.24 sec. The conclusions of this study include sufficient speed, sufficient arm strength, sufficient leg strength, sit & reach flexibility is lacking, right ankle flexibility is sufficient, left is lacking, upper body flexibility is very good, sufficient endurance, sufficient arm explosive power, sufficient leg explosive power, sufficient balance, sufficient coordination, and sufficient agility.